Palladium‐Catalyzed Aerobic Oxidative Cross‐Esterification of Aldehydes with Alcohols. Issue 11 (29th August 2017) - Gao, Meng; Chen, Meng; Li, Yang; Tang, Hong; Ding, Hao; Wang, Kai; Yang, Lingen; Li, Cuiting; Lei, Aiwen
Abstract: In this work, a palladium‐catalyzed oxidative esterification of aldehydes with alcohols was developed by using oxygen as the terminal oxidant. Various aldehydes and alcohols were selectively converted into their corresponding esters in good yields. Abstract : A bit of fresh air : A palladium‐catalyzed oxidative esterification of aldehydes with alcohols was developed by using oxygen as the terminal oxidant. Various aldehydes and alcohols were selectively converted into the corresponding esters in good yields.